Effect of Different UV Light Intensity on Porous Silicon Fabricated by Using Alternating Current photo-assisted Electrochemical Etching (ACPEC) Technique - Sohimee, Siti Nurfarhana; Hassan, Zainuriah; Ahmed, Naser Mahmoud; Lim, Way Foong; Quah, Hock Jin (2017)
Alternating current photo-assisted electrochemical etching (ACPEC) process was used to produce the formation of porous silicon with different ultra-violet(UV) light intensity. The study aims to investigate the effect of different UV light illumination on the properties of porous silicon. The surface of n-type silicon (111) was selectively etched in the HF and ethanol solution with ratio (5:20) for 30 minutes under different UV lamp intensity; 40%, 50% and 60%. The samples were characterized by using field emission scanning electron microscope (FESEM), atomic force microscopy (AFM) and high resolution X-ray diffraction (HR-XRD).